Transformational teaching in the information age : making why and how we teach relevant to students - Rosebrough, Thomas R. (ASCD, 2011)
This book focuses on the strategy that educators can utilize in the information age to create a relevant learning experience and educational opportunity by placing students at the center of learning. Uses theory, practice and real-world experiences to illustrate the importance of student-teacher relationships in a K-18 learning environment.